Prevalence and novel genetic characteristics of Cryptosporidium spp. in wild rodents in the northern foothills of the Dabie Mountains, southeast Henan Province, China. - Mengyao Yang; Yin Fu; Pitambar Dhakal; Zi Yan; Jiashu Lang; Chaofeng Ma; Yuhong Jiang; Congzhou Wang; Longxian Zhang (PLoS Neglected Tropical Diseases)
Background Cryptosporidium spp. are prevalent zoonotic pathogens that affect both humans and animals. The pathogens are spread through feces and represent a major cause of diarrhea. As they are both abundant and widely distributed, wild rodents play a significant role in the transmission of Cryptosporidium spp. The Dabie Mountains in southeast Henan Province are rich in wildlife resources as well as various species of livestock. However, the epidemiological characteristics of Cryptosporidium spp. among local wild rodents remain poorly understood. Therefore, the infection rate and genetic characteristics of Cryptosporidium spp. in wild rodents within this region should be determined. Methods Between March 2023 and April 2024, a total of 267 wild rodents were captured in the northern foothills of the Dabie Mountains, and fecal samples were collected from their intestines for DNA extraction. Species identification of wild rodents was conducted using PCR amplification of the universal vertebrate cytochrome b (cytb) gene. Nested PCR was subsequently used to amplify the small subunit (SSU) rRNA, actin, heat shock protein 70 (HSP70), and 60 kDa glycoprotein (gp60) genes for the analysis of Cryptosporidium species, genotypes, and subtypes in the fecal samples. Results The infection rate of Cryptosporidium spp. in wild rodents from the northern foothills of the Dabie Mountains was 21.3% (57/267). Seven species of wild rodents were identified, and the infection rates for Cryptosporidium spp. varied among host species. In particular, the infection rate was 21.4% (25/117) in Niviventer lotipes, 22.4% (22/98) in Apodemus agrarius, 17.2% (5/29) in Rattus nitidus, 22.2% (4/18) in Apodemus draco, and 33.3% (1/3) in Rattus tanezumi. The identification results indicated the presence of five Cryptosporidium species: Cryptosporidium apodemi (n = 12), C. ubiquitum (n = 11), C. viatorum (n = 7), C. ratti (n = 2), and C. occultus (n = 2). Moreover, two novel genotypes were identified: Cryptosporidium sp. rat genotype VI (n = 8) and Cryptosporidium sp. rat genotype VII (n = 15). Notably, a new subtype of C. viatorum designated as XVgA4 was discovered. Conclusions This study revealed the prevalence of Cryptosporidium spp. in wild rodents in the northern foothills of the Dabie Mountains and identified two novel Cryptosporidium genotypes, along with a new subtype, C. viatorum-XVgA4. The findings highlight the genetic diversity of Cryptosporidium spp., underscoring the increased risk of Cryptosporidium spp. transmission posed by local wild rodents population. It suggests that host-specific factors should be considered in epidemiological surveillance and control strategies of Cryptosporidium spp., which is of great significance for the prevention and control of Cryptosporidiosis.